The Evolution of Dong Small Songs and Cultural Change in Chinese Folk Music - Ping, Shiqi; Chuangprakhon, Sayam; Santaveesuk, Piyapun; You, Lin (Journal of Ecohumanism, 2024)
This study investigates the cultural evolution and contemporary significance of Dong’s small songs within the realm of Chinese folk music. Through ethnographic fieldwork, interviews, archival research, and thematic analysis, the historical roots and socio-cultural dynamics of Dong’s small songs are explored. The literature review delves into the cultural significance, historical evolution, preservation efforts, and challenges faced by Dong small songs, highlighting their role in reflecting regional identities and cultural change. The material and methods section outlines the qualitative research approach, including participant observation, semi-structured interviews, and archival data collection. The research results illuminate the multifaceted nature of Dong small songs, showcasing their adaptability, transmission processes, and contemporary expressions. Suggestions for future research emphasize the need for continued preservation efforts, innovative presentation platforms, and collaborative initiatives to ensure the sustainability and appreciation of Dong’s small songs in the context of evolving cultural landscapes.